Development of integrated curriculum and teaching materials for science/engineering courses - Zain, Saidi; Ahmad, Zuraida; Ismail, Ahmad Faris; Machouche, Salah; Mohamad, Souad A.; Hasbullah, Nurul Fadzlin; Toha @ Tohara, Siti Fauziah (Zes Rokman Resources, 2016)
The research is an outcome of the Focus Group Discussion (FGD) held on 18-19 November 2014 on the effect of curriculum and teaching materials on the grounding of Islamic foundations into science/engineering education system and how to invest and further develop the integration of Revelation into science/engineering courses. The FGD involved active discussions with a total of 9 groups of participants. The participants include those who have been involved in the implementation of Islamization of Knowledge at the Centre for Foundation Studies (CFS) and Kulliyah of Engineering (KOE), both at IIUM as well as several members of PERINTIS (Malaysian Muslim Scientists Association - an NGO). Participants addressed many critical issues related to the curriculum and teaching materials used in the implementation of Islamization of Knowledge (IOK) in the teaching of science/engineering subjects in local education institutions. The research provides some input pertaining to the concepts, evaluation methods and the methodology of integration to be considered for the effective instruction of science for engineering students in the context of International Islamic University Malaysia. The research suggests two major steps to establish a solid foundation for the integration project. First, reviewing of the content of the existing curriculum and teaching materials from an Islamic perspective (in-content) parallel with Islamic courses. Second, reformulating and developing integrated curriculum and teaching materials that are in line with the objectives of IOK and able to create the ideal learning environment for the sciences with a holistic approach.